Stepwise connectivity paves the way to reveal functional network vulnerability in age‐related neurodegenerative disorders. (1st February 2022) - Basaia, Silvia; Agosta, Federica; Cividini, Camilla; Spinelli, Edoardo Gioele; Castelnovo, Veronica; Leocadi, Michela; Calderaro, Davide; Canu, Elisa; Filippi, Massimo
Abstract: Background: Ageing is the main risk factor for most neurodegenerative diseases and results in complex transformations of the human brain function. The aim of this study was to investigate how topological organization of the brain connectome changes with age using resting‐state functional MRI and stepwise functional connectivity (SFC) analyses. Method: 138 controls were recruited and divided into two groups according to age: 55 young (20‐30 years [YC]) and 83 old (41‐84 years [OC]). SFC analysis aims to characterize regions that connect to specific seed brain areas at different levels of link‐step distances. Eight well‐known hubs of the human connectome were selected as seeds: middle frontal gyrus, rostral anterior and posterior cingulate cortex, precuneus, inferior parietal, middle temporal and lingual gyri and pericalcarine cortex. Whole‐brain two‐sample t‐test comparisons between groups were performed. Result: At one‐link step distance, in OC, all the seed regions displayed decreased regional–local functional connectivity with superior frontal and medial orbital frontal gyri, rostral anterior and isthmus cingulate cortex, precuneus and middle and inferior temporal gyri relative to YC; across intermediate link‐steps, a reduced connectivity was observed between all seed regions and frontal‐parietal lobes. By contrast, at the first link‐step distance, YC showed lower connectivity only between few seed regions and precentral, paracentral and lateral occipital gyri compared to OC. At intermediate link‐step distances, increased connectivity with sensorimotor regions was found in OC relative to YC. Conclusion: SFC approach might have important implication providing a starting point for evaluating network disruptions in age‐related neurodegenerative disorders. European Research Council (StG‐2016_714388_NeuroTRACK).